Aplicación contable en la “Industria de adoquines y bloques INDABLOK” de la Ciudad de Loja. Período del 01 de septiembre al 31 de diciembre del 2017 - Torres Jiménez, Cinthya Lizbeth (2019)
The industrial sector is one of the fundamental pillars for the economic and social development by means of the productive processes, nevertheless in many of the cases the adequate management of the costs is not given so much in raw material, labor and in the indirect costs of manufacture, reason why some industrial companies have been stagnant within the competitive advantages as for the control systems, before this the present investigative work called: "Accounting application in the "Industry of pavers and blocks INDABLOK" of the City of Loja was proposed. Period from September 1 to December 31, 2017", whose objective is to apply accounting in the industry for the period mentioned above, for which an inventory was prepared that reflects the assets, values and obligations it owns; also the design of a Plan and Manual of accounts in accordance with production activities, based on its policies, nature and objectives, as well as the preparation of auxiliary documents for recording costs such as: Production Orders, Requisition Orders, Time Cards, Workers' Forms, Cost Sheet, Payment Roles, Kárdex cards that will serve to keep track of your operations; and the respective execution of the accounting process until the conclusion of the Financial Statements, to finally proceed to the application of financial indicators, which will allow the owner manager to make the best decisions for his industrial growth. Therefore, the methodology used for the present thesis was basically based on the compilation of relevant and necessary information for the development of the same, through the application of cost accounting to carry out an adequate control of the cost elements and their distribution, both to determine the inputs and outputs of the materials used in the manufacture of the product, as well as the registration of labor and a budget of indirect costs applied to the productive process. 5 Likewise, according to the results found, it can be concluded that the lack of auxiliary records in the industry and the lack of an accounting process have been an obstacle to the manager-owner not being fully aware of all the accounting movements that are carried out in accordance with the activities produced, so they proceeded to prepare and execute them, in order to develop an adequate control of the production process and all the costs incurred in it, so that the current situation of the industry can be seen and this thesis can become a guide to improve the control of its resources.